Evaluating The Dimensions Of The Marketing Reengineering In The Syrian Public Banks And Their Reflection On The Quality Of Banking Service (Latakia University Journal - Economic and Legal Sciences Series, 2021)
Re-engineering Process is one of the contemporary administrative approaches to address administrative problems and this means a total transformation in work procedures and an unrestricted redesign of all management systems, used technology, commercial processes, organizational structure and organizational culture within the organization with the aim of achieving qualitative leaps in performance for all business joints of the organization.The research aims to study the relationship between the dimensions of marketing engineering (the organizational dimension, the human resource dimension and administrative empowerment, after information technology, the strategic dimension) and the quality of banking service in the branches of public Syrian banks in the Lattakia governorate, and to achieve this, two main hypotheses were formulated, and the researcher used the method of the questionnaire to collect The data analyzed using statistical tests, the most important of which are: the One-Sample T. test, the Pearson Correlation test, and the regression analysis. There is a weak overall assessment of the quality of banking services provided by the public banks under study, and there is also a moderate direct relationship between both the organizational dimension after the human resource and the technology dimension and between the quality of banking services in the banks under study, while there is a good relationship between the strategic dimension and the level of quality of banking services.